Comparison of two different tunnelling methods in hard rock - With a focus on the geological parameters - Aria, Hanieh (My University, 2021)
This report aimed to study two tunnelling excavation methods, Tunnelling Boring Machine (TBM) and Drilling and Blasting (D&B), to provide a decision basis to determine which excavation method is more suitable in hard rock. First, the two different excavation methods have been described, and the main factors that have influenced the choice of tunnelling method have been identified. To find these factors, the two excavations method was compared, focusing on how the geological parameter affects the tunnelling method. The most important parameters and factors have been presented to describe how they influence the two tunnelling methods. The lists of parameters are based on the performed literature study. A recently designed project, the Oslo–Skien railway tunnel, has been used as an example of a tunnelling project. This tunnel has been studied to find which factors affect the tunnelling method and why the TBM method was selected. This study will provide a practical example of TBM and an opportunity to investigate the suggested tunnelling method. A planned water tunnel between Vättern and Hallsberg has been investigated as a case study. A pre-study of this planned water tunnel based on identified parameters are used to suggest a primary excavation method. A definitive answer to the question about which driving method should be chosen is complicated. Concerning the geological condition of the water tunnel use, the TBM method seems to be a suitable option for water tunnels. For example, the estimated average advance rate for the water tunnel using the TBM method is about 65m/week and about 39m/week with the D&B method. Investigating other factors that influenced the tunnelling method, such as equipment parameters and construction processes, recommended increasing the probability of which tunnelling method is most suitable.
Keywords: Excavation; geological parameter and advance rate; TBM; D&B